2017
DOI: 10.18632/oncotarget.20365
|View full text |Cite
|
Sign up to set email alerts
|

MLACP: machine-learning-based prediction of anticancer peptides

Abstract: Cancer is the second leading cause of death globally, and use of therapeutic peptides to target and kill cancer cells has received considerable attention in recent years. Identification of anticancer peptides (ACPs) through wet-lab experimentation is expensive and often time consuming; therefore, development of an efficient computational method is essential to identify potential ACP candidates prior to in vitro experimentation. In this study, we developed support vector machine- and random forest-based machine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
199
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(202 citation statements)
references
References 72 publications
3
199
0
Order By: Relevance
“…Results from the compositional analyses suggested that integrating the amino acid preference information would be helpful for differentiating between DHSs and non-DHSs, and so, we used these as input features for ML methods to improve classification. The major advantage of ML methods is their ability to consider multiple features simultaneously, often capturing hidden relationships [16][17][18][19][20][21][22][23].…”
Section: Compositional Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Results from the compositional analyses suggested that integrating the amino acid preference information would be helpful for differentiating between DHSs and non-DHSs, and so, we used these as input features for ML methods to improve classification. The major advantage of ML methods is their ability to consider multiple features simultaneously, often capturing hidden relationships [16][17][18][19][20][21][22][23].…”
Section: Compositional Analysismentioning
confidence: 99%
“…In the second step of the previous section, we used three different ML-based methods instead of SVM, including, RF, ET, and k-NN. A detailed description of the development of prediction models using these methods was provided in our recent studies [21,23]. For each ML-based method, we generated 33 prediction models using different sets of features, including individual composition, hybrid models, and features based on FIS cut-off.…”
Section: Comparison Of Three Ml-based Models With the Svm-based Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer is the second leading cause of death in the world. Therefore, the screening of specific lectins from a large number of lectins is of great significance not only for the discovery of tumor markers and cancer treatment, but also for better understanding and conquering cancer (Balachandran et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, several methods to predict therapeutic properties of a protein or peptide such as anti-cancer, anti-microbial, anti-bacterial, anti-fungal, anti-tubercular, anti-hypertensive, toxic, tumor homing etc. have been developed (Manavalan et al, 2017;Tyagi et al, 2013;Meher et al, 2017;Lata, Mishra, and G. P. S. Raghava, 2010;Agrawal et al, 2018;Usmani, Bhalla, et al, 2018;Kumar et al, 2015;Manavalan et al, 2018;Gupta et al, 2013;Sharma et al, 2013). These peptides/proteins have therapeutic properties thus play vital role in designing proteins/peptide-based drugs and vaccines (Dhanda et al, 2017;Usmani, Kumar, et al, 2018;Nagpal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%